A mechanistic link between STM and CUC1 during Arabidopsis development - Spinelli, Silvana Virginia (2011)
The KNOXI transcription factor SHOOT MERISTEMLESS (STM) is required to establish and maintain the Arabidopsis (Arabidopsis thaliana) apical meristem, yet little is known about its direct targets. Using different approaches we demonstrate that the induction of STM causes a significant up-regulation of the organ boundary gene CUP SHAPED COTYLEDON1 (CUC1), which is specific and independent of other meristem regulators. We further show that the regulation of CUC1 by STM is direct and identify putative binding sites in its promoter. Continuous expression of STM in Arabidopsis leaf primordia also causes the activation of CUC2-3, as well as microRNA MIR164a, which provides a negative feedback loop by posttranscriptionally regulating CUC1 and CUC2. The results bring new insights into the mechanistic links between KNOXI and CUC transcription factors and contribute to the understanding of the regulatory network controlled by STM.